Past, present, and future of stroke in middle‐income countries: the Brazilian experience. (22nd May 2013) - Martins, Sheila Cristina Ouriques; Pontes‐Neto, Octávio Marques; Alves, Cloer Vescia; de Freitas, Gabriel Rodriguez; Filho, Jamary Oliveira; Tosta, Elza Dias; Cabral, Norberto Luiz; ,
Abstract : Background: Stroke is one of the major public health challenges in middle‐income countries. Brazil is the world's sixth largest economy but was clearly behind the milestones in the fight against stroke, which is the leading cause of death and disability in the country. Nevertheless, many initiatives are now reshaping stroke prevention, care, and rehabilitation in the country. Aims: The present article discusses the evolution of stroke care in Brazil over the last decade. Methods: We describe the main characteristics of stroke care before 2008; a pilot study in a Southern Brazilian city between 2008 and 2010, the Brazilian Stroke Project initiative; and the 2012 National Stroke Policy Act. Results: The National Stroke Project was followed by a major increased on the number of stroke center in the country. The key elements of the 2012 National Stroke Policy Act included: definition of the requirements and levels of stroke centers; improved reimbursement for stroke care; promotion of stroke telemedicine; definition of the Line of Stroke Care (to integrate available resources and other health programs); increased funding for stroke rehabilitation; funding for training of healthcare professionals and initiatives to increase awareness about stroke within the population. Conclusions: The evolution of stroke care in Brazil over the last decade is a pathway that exemplifies the challenges that middle‐income countries have to face in order to improve stroke prevention, treatment and rehabilitation. The reported Brazilian experience can be extrapolated to understand the past, present, and future of stroke care in middle‐income countries.